2002
DOI: 10.1148/radiol.2221001599
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: Detection with Gadolinium- and Ferumoxides-enhanced MR Imaging of the Liver

Abstract: For the detection of early HCC, gadolinium-enhanced MR imaging is preferred to ferumoxides-enhanced MR imaging because the former demonstrated significantly greater accuracy in the detection of small HCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 23 publications
0
45
0
8
Order By: Relevance
“…A 3D gradient-echo sequence and parallel acquisition techniques facilitate dynamic contrast-enhanced imaging of HCC [7][8][9][10][11][12]. Gadobenate dimeglumine has been found useful for liver MRI.…”
Section: Choi Et Almentioning
confidence: 99%
“…A 3D gradient-echo sequence and parallel acquisition techniques facilitate dynamic contrast-enhanced imaging of HCC [7][8][9][10][11][12]. Gadobenate dimeglumine has been found useful for liver MRI.…”
Section: Choi Et Almentioning
confidence: 99%
“…Difficulties can be observed in distinguishing well differentiated HCC from regenerative and dysplastic nodules, because small HCCs can have an identical appearance as dysplastic nodules, in up to 13% [26]. HCCs show variable enhancement with superparamagnetic iron oxide (SPIO) particles, therefore in the context of cirrhosis and small tumors, gadolinium enhanced imaging or a combination of the two types of contrast agent are preferred [27,28]. In our study, the incapacity of MRI to distinguish HCC depended on enhancement patterns and grading.…”
Section: Discussionmentioning
confidence: 99%
“…Pauleit et al reported that the detection of small HCC (Å15 mm) in SPIO-enhanced MRI was inferior to that of large HCC. 8 The following reasons might have contributed to the non-detection of small HCCs in SPIO-enhanced MRI. In cirrhotic liver parenchyma, the accumulation of SPIO particles in KupŠer cells decreases because of the decreasing activity of KupŠer cells.…”
Section: Discussionmentioning
confidence: 99%